Age-related differences in muscle recruitment and reaction-time performance - Arnold, Pauline; Vantieghem, Stijn; Gorus, Ellen; Lauwers, Elien; Fierens, Yves; Pool-Goudzwaard, Annelies; Bautmans, Ivan (Experimental gerontology, 2015)
Previously, we showed that prolonged reaction-time (RT) in older persons is related to increased antagonist muscle co-activation, occurring already before movement onset. Here, we studied whether a difference in temporal agonist and antagonist muscle activation exists between young and older persons during an RT-test. We studied Mm. Biceps (antagonist muscle) & Triceps (agonist muscle) Brachii activation time by sEMG in 60 young (26±3years) and 64 older (80±6years) community-dwelling subjects during a simple point-to-point RT-test (moving a finger using standardized elbow-extension from one pushbutton to another following a visual stimulus). RT was divided in pre-movement-time (PMT, time for stimulus processing) and movement-time (MT, time for motor response completion). Muscle activation time 1) following stimulus onset (PMAT) and 2) before movement onset (MAT) was calculated. PMAT for both muscles was significantly longer for the older subjects compared to the young (258±53ms versus 224±37ms, p=0.042 for Biceps and 280±70ms versus 218±43ms for Triceps, p<0.01). Longer agonist muscle PMAT was significantly related to worse PMT and RT in young (respectively r=0.76 & r=0.68, p<0.001) and elderly (respectively r=0.42 & r=0.40, p=0.001). In the older subjects we also found that the antagonist muscle activated significantly earlier than the agonist muscle (−22±55ms, p=0.003). We conclude that in older persons, besides the previously reported increased antagonist muscle co-activation, the muscle firing sequence is also profoundly altered. This is characterized by a delayed muscle activation following stimulus onset, and a significantly earlier recruitment of the antagonist muscle before movement onset.